Multi-level participatory consultative approach for institutional change in river basins: Lessons from the Deduru Oya Case Study in Sri Lanka - Jinapala, K.; Somaratne, Pallewatte G.; Perera, L.R.; Makin, Ian W.; Bandaragoda, Don Jayatissa (International Water Management Institute, 2003)
This paper discusses methodologies applied in the Deduru Oya river basin, the basin selected from Sri Lanka for the regional study on the development of effective water management institutions. The study was funded by the Asian Development Bank (ADB) to assist the five countries, Indonesia, the Philippines, Nepal, China and Sri Lanka to work out methodologies and develop effective water management institutions (ADB-RETA 5812). The Deduru Oya basin in which the empirical studies were carried out is located in the northwestern province of Sri Lanka. The methodology discussed in this paper includes mainly the approaches adopted for stakeholder consultation and other data collection methods for identifying water resources management problems in the basin. The findings of the various special studies carried out are not included in this paper and instead, the relevance of information generated through such studies to hold useful participatory stakeholder consultations are highlighted. The information generated through special studies became useful, facilitating inputs for the successful implementation of stakeholder consultation activities.